Substratos e fertirrigação na produção de mudas de Anadenanthera macrocarpa (Benth.) Brenan e Cedrela odorata L. - Uliana, Marcelo Bortoli (2009)
The growing demand for seedlings of forest native sorts has been demanding inquiries made a list to the use of substrates and fertirrigação, able to provide seedlings that present elevated rates of initial growth and of survival after the planting to the least possible cost. In this context, this work intended to contribute to identify the best frequency of fertirrigação, better substrate as well as the time of permanence of the seedlings of the sorts of angico and cedro rosa. The study was carried out in the Experimental Station of the UNIOESTE, Campus of Marechal Candido Rondon, PR. The experimental used delineation was in blocks at random, in arrangement of subdivided pieces, taking four frequencies as a principal piece of fertirrigação (0; 7; 14 and 21 days) and in the subpieces four types of substrates (commercial Substrate, Mixture of BCD H (7:3 v:v); Mixture of BCD V TO, (7:2:1 v:v:v); and Mixture of BCD V (7:3 v:v)), with four repetitions. They were valued the height of plant, diameter of I collect, foliaceous area, dry mass of the air part, root and total, relation breaks air / root, quality rate of DICKSON, rate of absolute growth and condutividade of the substrate. These parameters were valued to 50, 80, 110, 140 and 170 days after emergence of the plantules. Through the analysis of the obtained results, it was ended that for the best development of seedlings of angico and pink cedar recommends to itself to do the fertirrigação to each 14 days, as soon as the interval presented better results in several parameters. The seedlings of angico can go for the field after 140 days while the seedlings of cedar can go to 110 days. The mixture of pulp of cane when more humus (7:3 was analysed; v:v) it provided the best development of the seedlings Anadenanthera macrocarpa (Benth.) Brenan; (angico vermelho) and of Cedrela odorata L (cedro rosa)